Commandaria Sweet Wine Melanoidins as Functional Food Ingredient: Exploring Antioxidant, Antimicrobial and Anti-hypertensive Potential. - Goulas, Vlasios (My University, 2018)
Background & aims: Melanoidins are high molecular-weight, brown-colored and nitrogen-containing compounds generated in the late stages of the Maillard reaction. These compounds are mainly responsible for specific color and typical appearance of thermally processed foods. The aim of this work was to study the functional properties of the melanoidins isolated from Commandaria, a straw sweet wine.